The role of autoimmune antibodies to predict secondary autoimmunity in patients with relapsing-remitting multiple sclerosis treated with alemtuzumab: A nationwide prospective survey - Sandgren, Sofia; Novakova, Lenka; Axelsson, Markus; Amirbeagi, Firoozeh; Kockum, Ingrid; Olsson, Tomas; Malmestrom, Clas; Lycke, Jan (Frontiers in Neurology, 2023)
Background Alemtuzumab (ALZ) is an immune reconstitution therapy for treating relapsing-remitting multiple sclerosis (RRMS). However, ALZ increases the risk of secondary autoimmune diseases (SADs). Objective We explored whether the detection of autoimmune antibodies (auto-Abs) could predict the development of SADs. Methods We included all patients with RRMS in Sweden who initiated ALZ treatment (n = 124, 74 female subjects) from 2009 to 2019. The presence of auto-Abs was determined in plasma samples obtained at the baseline and at 6, 12, and 24 months of follow-up, as well as in a subgroup of patients (n = 51), it was determined in plasma samples obtained at the remaining 3-month intervals up to 24 months. Monthly blood tests, urine tests, and the assessment of clinical symptoms were performed for monitoring safety including that of SADs. Results Autoimmune thyroid disease (AITD) developed in 40% of patients, within a median follow-up of 4.5 years. Thyroid auto-Abs were detected in 62% of patients with AITD. The presence of thyrotropin receptor antibodies (TRAbs) at the baseline increased the risk of AITD by 50%. At 24 months, thyroid auto-Abs were detected in 27 patients, and 93% (25/27) developed AITD. Among patients without thyroid auto-Abs, only 30% (15/51) developed AITD (p < 0.0001). In the subgroup of patients (n = 51) with more frequent sampling for auto-Abs, 27 patients developed ALZ-induced AITD, and 19 of them had detectable thyroid auto-Abs prior to the AITD onset, with a median interval of 216 days. Eight patients (6.5%) developed non-thyroid SAD, and none had detectable non-thyroid auto-Abs. Conclusion We conclude that monitoring thyroid auto-Abs, essentially TRAbs, may improve the surveillance of AITD associated with ALZ treatment. The risk for non-thyroid SADs was low, and monitoring non-thyroid auto-Abs did not seem to provide any additional information for predicting non-thyroid SADs.